1998
DOI: 10.1021/bi981633h
|View full text |Cite
|
Sign up to set email alerts
|

Two Substrate Interaction Sites in Lignin Peroxidase Revealed by Site-Directed Mutagenesis

Abstract: It has been shown recently that Trp171 of lignin peroxidase (LiP) is hydroxylated at the Cbeta position [Blodig, W., Doyle, W. A., Smith, A. T., Winterhalter, K., Choinowski, T., and Piontek, K. (1998) Biochemistry 37, 8832-8838]. Comparative experiments, carried out on both wild-type fungal and recombinant LiP isoenzyme H8 (LiPH8), indicate that the process of hydroxylation is autocatalytic and that Trp171 may be implicated in catalysis. The role of this residue has therefore been examined using site-directed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
218
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 239 publications
(230 citation statements)
references
References 40 publications
11
218
0
1
Order By: Relevance
“…An exposed oxidation site has been demonstrated extensively in a related heme enzyme viz. lignin peroxidase, where a hydroxylated tryptophan residue carries out the electron withdrawal from substrate molecules (43)(44)(45). In an electron density map of lignin peroxidase from Phanerochaete chrysosporium, strong electron density showed a hydroxylation at the C␤ position of the surfaceexposed Trp-171.…”
Section: Resultsmentioning
confidence: 99%
“…An exposed oxidation site has been demonstrated extensively in a related heme enzyme viz. lignin peroxidase, where a hydroxylated tryptophan residue carries out the electron withdrawal from substrate molecules (43)(44)(45). In an electron density map of lignin peroxidase from Phanerochaete chrysosporium, strong electron density showed a hydroxylation at the C␤ position of the surfaceexposed Trp-171.…”
Section: Resultsmentioning
confidence: 99%
“…22 However, the extensive screening required to identify mutant production strains, as well as contamination with the native enzyme, led to disappointing results. The model bacterium Escherichia coli has been extensively developed as an expression platform for fungal enzymes, and many recombinant enzymes have been isolated successfully from inclusion bodies and refolded with 1-28% efficiency [23][24][25][26][27][28][29][30] and maximum yields of 1.5-14 mg L ¡1 after in vitro activation and purification. 29 A soluble form of a VP was produced using a thioredoxin tag 31,32 or following intensive screening.…”
Section: Recombinant Lignin-degrading Peroxidasesmentioning
confidence: 99%
“…However, the degradation of these simple aromatic compounds may require different catalytic mechanisms, which makes it difficult to extrapolate the results to typical lignin and lignocellulose samples. For example, LiP has two substrate interaction sites: a heme-edge site which is typical for peroxidases and a second site for the oxidation of VA. 24 The optimization of enzyme activity by screening will only select for increases in activity against the test substrate under the specific conditions of the test and will not necessarily have a positive impact on the degradation of typical lignin substrates found in plant biomass or organosolv lignin. It is also clear that the successful degradation of lignin and lignocellulose requires multiple peroxidases and other lignin-degrading enzymes and accessory proteins.…”
Section: Future Challengesmentioning
confidence: 99%
“…Doyle and his group 19) recently found that , degrades the nonphenolic lignin model veratrylglycerol-β -guaiacyl ether yielding veratryl aldehyde, and oxidizes veratryl alcohol and p-dimethoxybenzene to veratryl aldehyde and p-benzoquinone respectively as LiP does. A review on lignin conversion by MnP has been published recently.…”
Section: )-6)mentioning
confidence: 99%
“…Doyle and his group 19) recently found that by cultivating wood-rotting fungi in an agar medium containing several phenolic compounds, such as gallic acid, tannic acid, and hydroquinone, that white-rot fungi produced a large darkened zone around the mycerial mat, but no zone of darkening was associated with the growth of brown-rot fungi. Davidson et al 37) subsequently investigated the reaction using 210 species of wood-rotting fungi, and concluded that the white-rotting type coincides with Bavendamm's reaction in general, and that the reaction is helpful in identifying fungi.…”
mentioning
confidence: 99%